AM1* parameters for manganese and iron - Kayi, Hakan; Clark, Timothy (Journal of Molecular Modeling, 2010)
We report the parameterization of AM1* for the elements manganese and iron. The basis sets for both metals contain one set each of s-, p- and d-orbitals. AM1* parameters are now available for H, C, N, O and F (which use the original AM1 parameters), Al, Si, P, S, Cl, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Br, Zr, Mo, I and Au. The performance and typical errors of AM1* are discussed for Mn and Fe, and are compared with available NDDO Hamiltonians.